Temporal distribution of blowflies of forensic importance (Diptera: Calliphoridae), in man-size domestic pigs carcasses, in the Forest Reserve Adolpho Ducke, Manaus, Amazonas, Brazil - Ururahy-Rodrigues, Alexandre; Rafael, José Albertino; Pujol-Luz, José Roberto (EntomoBrasilis, 2013)
One of the must forensic importance insect families is Calliphoridae (Diptera) and different species of this family were used to demonstrate the efficiency of the experimental model used in this study. The experiments were performed with domestic pig models (approximately 60 kg) in Adolpho Ducke Forest Reserve (Manaus, Amazonas). To minimize the effect of repeated samplings in the same model (a result of pseudoreplication), two models were used to answer two questions: 1) What is the species composition and temporal distribution of Calliphoridae adults? 2) What is the species composition and temporal distribution of Calliphoridae that effectively colonized the carcass? Six pseudoreplicates were studied in three periods: from 06/30/2005 to 07/30/2005 (less rainy season), from 10/18/2005 to 11/17/2005 (transition period between the two seasons) and from 03/15/2006 to 04/14/2006 (rainy season). The immatures and adults collected were identified as forensic indicators. The decomposition process presented five stages (fresh, bloated, decay, adipocere-like and skeletonization). The first four days included the first three stages of decomposition and were the most attractive to the Calliphoridae. The three taxa that were most abundant, regular and with highest peaks in the first four samples of each experiment were, in ascending order: Hemilucilia semidiaphana (Rondani), Hemilucilia segmentaria (Fabricius) e Paralucilia spp.. Linear regressions showed low values of F and high values of P, indicating that rain did not influence the sampling results. Distribuição Temporal de Moscas Varejeiras de Importância Forense (Diptera: Calliphoridae), em Porcos Domésticos, com Massa Corporal Comparável ao de um ser Humano Adulto, na Reserva Florestal Adolpho Ducke, Manaus, Amazonas, Brasil Resumo. Uma das famílias de insetos de maior importância forense é Calliphoridae (Diptera). Diferentes espécies dessa família foram utilizados para descrever a eficiência da modelagem experimental aplicada neste estudo. Porcos domésticos foram utilizados como modelos (aproximadamente 60 kg), em Manaus, Amazonas, na Reserva Floresta Adolpho Ducke. Para minimizar o efeito das coletas repetidas no mesmo modelo (consequência da pseudoreplicação), foram utilizados simultaneamente dois modelos para responder duas perguntas: 1) Qual a composição e a distribuição temporal dos califorídeos adultos? 2) Qual a composição e a distribuição temporal dos califorídeos que efetivamente colonizaram a carcaça? Foram estudadas seis pseudoréplicas em três períodos: de 30/06/2005 a 30/07/2005 (estação menos chuvosa); de 18/10/2005 a 17/11/2005 (transição entre as duas estações) e de 15/03/2006 a 14/04/2006 (estação mais chuvosa). As táxons coletados nos estágios adulto e imaturo, na carcaça, foram apontadas como indicadoras forenses. O processo de decomposição apresentou cinco estágios: fresco, inchamento, deterioração, saponificação e esqueletização.. Os primeiros quatro dias compreendem os três primeiros estágios do processo de decomposição e foram os mais atrativos para os califorídeos. Os três táxons mais abundantes, regulares e que apresentaram os maiores picos nas quatro primeiras coletas de cada experimento em ordem crescente foram, Hemilucilia semidiaphana (Rondani), Hemilucilia segmentaria (Fabricius) e Paralucilia spp.. Regressões lineares mostraram baixos valores de F e altos de P, indicando que a chuva não influenciou nos resultados das coletas.